Perancangan Analisis Risiko Sistem Manajemen Mutu ISO 9001 : 2015 di PT. X - Ricky Kurniawan; I Nyoman Sutapa (Jurnal Titra, 2018)
PT. X is a company engaged in the field of bodybuilding. This study aims to design risk analysis and documents related to the interests to complete the requirements of ISO 9001: 2015 quality management system at PT. X. The preliminary quality review indicates compliance of 61% before designing for the ISO 9001: 2015 quality management system. The design of risk analysis for ISO 9001: 2015 quality management system using Failure Mode and Effect Analysis (FMEA) method. This research is still in the design stage and implemented on all departments in PT. X except the accounting and finance department. The result of risk analysis design with FMEA method shows that the biggest risk in PT. X is in the warehouse department, QC, production, and marketing. The final quality review after the design of the quality management system shows a suitability of 91% against the requirements of ISO 9001: 2015.